Embedding simulation education into the engineering management body of knowledge. (26th May 2009) - Tolk, Andreas; Rabadi, Ghaith; Merino, Donald N.
The American Society for Engineering Management (ASEM) established a Body of Knowledge (BoK). As simulation is of growing interest to engineers in general and to engineering managers in particular, simulation is part of this documentation of domains of interest that characterise the profession. The basis for the Body of Knowledge comprises of established and accredited curricula and additional input from practitioners of the field. As it is essential to cover the basic topics and core competences as well as application specific domain knowledge, the simulation education for engineers is categorised into topics on simulation theory and simulation application.